ISOLASI DAN IDENTIFIKASI Shigella sp. PENYEBAB DIARE PADA BALITA - Fitratul Aini (Biology Department, Faculty of Science and Technology, Univeristas Jambi, Indonesia, 2018)
Diarrhea is the highest cause of death for toddlers. This study aims to isolate and identify the bacteria Shigella sp. causes of diarrhea in toddlers. Diarrhea samples were obtained from RSIA Annisa, Jambi City then isolation was carried out at the Biotechnology and Engineering Laboratory of the Faculty of Science and Technology, Jambi University using SSA media and dilution and biochemical tests were carried out. The results of bacterial isolates were characterized and obtained by Salmonella sp. isolates. With the characteristic of black colonies, capable produce H2S gas and can ferment sugar.